Analysis Of Protein, Fat and Carbohydrate Nutrients in F100-Based Processed Cookies with Corn Flour Substitution for Malnourished Toddlers - Shannaz Dea Puspita Lengkong; Sunarto Kadir; Ayu Rofia Nurfadillah (Universitas Muhammadiyah Palu, 2026)
Nutrient intake is an important factor for the growth and development of toddlers, one of the causes of malnutrition in toddlers is a suboptimal feeding pattern. Problem formulation, what is the content of protein, fat, and carbohydrates and how the panelists received based on organoleptic tests on processed F100-based cookies with 10%, 20%, and 30% corn flour substitution for malnourished toddlers. The purpose of the study was to determine the content of protein, fat, and carbohydrates as well as the acceptance of panelists based on organoleptic tests on processed F100-based cookies with 10%, 20% and 30% corn flour substitution for malnourished toddlers. This type of research is quantitative by using laboratory experiments to analyze protein, fat, and carbohydrate levels. The research design used was a 1-factorial Complete Random Design (RAL) with 3 treatments (10%, 20%, and 30%). The research panelists consisted of 20 students of Public Health specializing in nutrition to determine the level of organoleptic acceptance of cookies. Data were analyzed using univariate analysis. The results of the nutrient analysis research obtained protein content of 8.29%, 9.12%, and 9.58% for each treatment, fat content of 10.10%, 11.15%, and 12.25% for each treatment and carbohydrate content of 76.12%, 73.82%, and 71.83% for each treatment. The results of organoleptic tests showed that the entire cookie formulation was well received by the panelists, especially at 30% substitution.In conclusion, the nutritional content of corn flour substitution cookies can be an alternative in meeting the nutritional needs of toddlers per day. The suggestion for the next researcher is to conduct several follow-up tests to determine the content of micronutrients (vitamins and minerals).